Outcome of a public consultation on the draft scientific opinion on the health risks related to the presence of cyanogenic glycosides in foods other than raw apricot kernels. Issue 4 (11th April 2019) - ,
Abstract : The European Food Safety Authority (EFSA) carried out a public consultation to receive input from the interested parties on a draft scientific opinion on the health risks related to the presence of cyanogenic glycosides in foods other than raw apricot kernels prepared by the EFSA Panel on Contaminants in the Food Chain (CONTAM Panel), supported by the Working Group on hydrocyanic acid in food. The draft opinion was endorsed by the CONTAM Panel for public consultation at its plenary meeting on 14 November 2018. The written public consultation was open from 27 November 2018 to 25 January 2019. EFSA received comments from seven different interested parties. EFSA and its CONTAM Panel wish to thank all stakeholders for their contributions. The present report contains the comments received and explains the way they have been considered for finalisation of the opinion. The opinion was adopted at the CONTAM Plenary meeting on 19 March 2019 and published in the EFSA Journal. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5662/full